PENDAPATAN KELUARGA SEBAGAI MODAL PENDIDIKAN ANAK DI DUSUN GUMUK AGUNG DESA GINTANGAN KECAMATAN ROGOJAMPI KABUPATEN BANYUWANGI - Abdul Shomad; Topan Priananda Adinata (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2017)
This study to assess family income with the level of education of children with the emancipatory quality approach shows that meeting the main needs that must be obtained is money. Indirectly money becomes the primary need of every person who is more specifically called income. Family income contributes to education and education capital. Family income in Gumuk Hamlet is obtained from handicrafts, plantations, and agricultural commodities.